Implementation of Information and Communication Technology Innovation Policy through E-Government in Public Services - Amartina, Rahma Yudi; Rahmanto, Andre Noevi; Naini, Albert Muhammad Isrun (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of information and communication technology encourages changes in community activities in various sectors. One of them is in the public service sector brought by the government through e-government. This research aims to discover how information and communication technology innovation policies are implemented through e-government in public services. The method used in this research is Systematic Literature Review (SLR) from the Google Scholar site within the year of 2012-2023. From the search results, a selection process was performed, resulting in 20 journals for analysis. The research results show that many of the current researchers are focusing on e-government, specifically regarding public services at the local government level. Interviews and observations are widely used data collection techniques. Elements that help the implementation of e-authorities offerings in public offerings are supported via way of means of a organized bureaucratic structure, making plans and a centralized and ok system. Obstacles for the implementation of e-authorities offerings in public offerings are encouraged via way of means of the exceptional of human resources, incomplete making plans, the exceptional of centers and infrastructure, and public recognition of e-authorities itself